Evaluating the impact of smoking on the risk of dry eye disease: a two-sample Mendelian randomization study - Kuiliang Yang; Han Zhang; Yujin Wang; Yulin Yan; Zixian Yang; Shanshan Wan; Wanju Yang; Yanning Yang (Scientific Reports)
Abstract Dry Eye Disease (DED) is a common condition worldwide, with smoking being recognized as a possible aggravating factor. Although observational studies have indicated a potential correlation, the findings have been inconclusive. In the study, Mendelian randomization (MR) analysis is used to investigate this potential causal relationship. Adhering to STROBE-MR guidelines, a MR analysis was conducted using genetic instrumental variables from Genome-wide association studies (GWAS). The research investigated the impact of various smoking-related exposures (regular smoking, lifetime smoking, smoking intensity, and smoking cessation) on DED as an outcome. Three distinct methodologies were employed: the inverse variance weighted (IVW) method, the MR-Egger method, and the weighted median (WM) method. To ensure the robustness of the MR results, sensitivity analyses were conducted. In MR analyses, it was observed that both lifetime smoking and regular smoking were associated with a significant increase in the risk of DED (IVW method: P < 0.05). The results indicated that the odds ratios (ORs) for lifetime smoking and regular smoking in relation to DED were 1.757 (95% CI 1.021–3.025) and 2.121 (95% CI 1.017–4.423), respectively. However, there was no significant correlation found between smoking intensity, cessation, and the risk of DED. This study presents genetic evidence indicating that long-term smoking could potentially be a causal risk factor for DED. Subsequent research will need to conduct specifically designed randomized controlled trials to further investigate this association.